Functional insights from genetic channelopathies - Schorge, Stephanie (Henry Stewart Talks, 2014)
Channelopathies in the Genomic Era, Introduction to ion channels, The example of Hyperekplexia, Transcriptional regulation defects of ion channels are associated with cases of schizophrenia and epilepsy, Ion channels mRNA processing in myotonia congentia and epilepsy, Ion channel misfolding and episodic ataxia type 1, Ion channel mistrafficking and epilepsy, Ion channel degradation and Spinocerebellar ataxia type 6, concluding remarks